Severe endogenous endophthalmitis with panophthalmitis-lessons to learn - Teo, BH; Safinaz Mohd Khialdin; Umi Kalthum MN; Wan Haslina WAH (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Endogenous endophthalmitis is a devastating intraocular infection. Finding the primary infection and directed treatment is life-saving. We describe a 47-year-old man, with uncontrolled diabetes mellitus, who presented with two weeks history of progressive reduced vision and redness of the left eye (LE). He was generally unwell since a month, previously. Examination showed relative afferent pupillary defect (RAPD) in the affected eye and visual acuity was hand movement. There was moderate anterior chamber and vitreous reaction. Fundus examination showed a huge dome-shaped choroidal mass covering the entire macula. Diagnosis of severe endogenous endophthalmitis was made, with isolation of Enterobacter sp. from his blood culture. Meanwhile, he also had elevated inflammatory markers with presence of leucocytosis, neutrophilia and elevated erythrocyte sedimentation rate (ESR) as well as C-reactive protein (CRP). Vitreous tap and aqueous tap had no growth, He improved with combination of intravitreal and systemic antibiotic, as shown by the resolved fever and reduced inflammatory markers but progressive inflammation occluded the fundus details and the LE vision eventually became no projection of light despite treatment. Subsequently, he developed rubeotic glaucoma and was treated conservatively because the LE was painless with poor vision. The repeated blood culture and urine was normal. In conclusion, endogenous endophthalmitis with eventual panophthalmitis is difficult to treat and has very poor visual prognosis. Our case highlights the challenges faced in the management of vision-threatening endophthalmitis and panophthalmitis in this patient.